Larvicidal, adulticidal, and oviposition-deterrent activity of Piper betle L. essential oil to Aedes aegypti - Martianasari, Riesna (Vet World, 2019)
BACKGROUND AND AIM: Aedes aegypti is a primary vector of many arthropod-borne diseases. One of the diseases, dengue fever, is an endemic disease in Indonesia causing high mortalities for decades. There are no preventive and specific treatments for dengue so far. Therefore, prevention of this disease largely depends on the mosquito control. Since resistance to chemical insecticides occurred worldwide, the study on alternate and new mosquito insecticides are mandatory. This study aimed to demonstrate the effect of essential oil from P. betle L. in the larval and adult stages, as well as its influence on oviposition activity of A. aegypti mosquito. MATERIALS AND METHODS: P. betle efficacy was evaluated in various stages of A. aegypti development. For the larvicidal activity, larvae instar III stage was used. Adulticidal assay in this experiment was performed using newly emerged A. aegypti. For oviposition assay, mated A. aegypti was tested for their responses to P. betle-treated and non-treated ovitraps. RESULTS: P. betle L. - adulticide activity was effective with a concentration of 2.5 μl/ml, caused 100% mortality within 15-30 min. Larvicide activity was observed after 1 h, 24 h, and 48 h post-treatment with LC(50)183, 92.7, and 59.8 ppm and LC(90) 637, 525, and 434.7 ppm, respectively. Oviposition activity index was −0.917 in 1000 ppm. In addition, the eggs number of A. aegypti oviposition with 100 ppm of essential oil P. betle L. was 5 times lower than the control. CONCLUSION: This study demonstrated clearly that essential oil derived from P. betle L. potentially acts as alternate bioinsecticide to control A. aegypti population. The application can be varied or combined in different stages of mosquito development.